Fiber optic communications : fundamentals and applications - Kumar, Shiva, Dr.; Deen, M. Jamal (Chichester, West Sussex, United Kingdom :: Wiley, 2014)
"This new title covers basic topics such as transmitters, fibers, amplifiers and receivers and details new developments such as nonlinear fiber-optic systems and nonlinear phase noise. Starting with a review of electromagnetics and optics, including Faraday's law and Maxwell's equation, it then moves on to provide information on optical fiber transmissions, laser oscillations, wave particle density and semiconductor laser diodes. This is followed up with chapters covering optical sources, optical modulators, optical receivers, including coherent receivers, and optical amplifiers. The final part of the book discusses performance analysis, channel multiplexing techniques, nonlinear effects and digital signal processing respectively"--
Includes bibliographical references and index.
Keywords: Optical fiber communication; Fiber optics; TECHNOLOGY & ENGINEERING / Optics